2002
DOI: 10.1002/cncr.10817
|View full text |Cite
|
Sign up to set email alerts
|

Expression of endothelial and inducible nitric oxide synthase in benign and malignant lesions of the breast and measurement of nitric oxide using electron paramagnetic resonance spectroscopy

Abstract: BACKGROUND Nitric oxide (NO) is present in various human solid tumors and tumor cell lines, and it is believed that NO plays an important role in tumor growth. An increased NO concentration catalyzed by NO synthase (NOS) is cytotoxic and can promote apoptosis. The expression of endothelial NOS (e‐NOS) and induced NOS (i‐NOS) was examined in various breast tumors. METHODS Immunohistochemical staining with a monoclonal antibody (Ab) against e‐NOS and a polyclonal Ab against i‐NOS was performed on paraffin embedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 24 publications
0
56
1
2
Order By: Relevance
“…However, a dichotomy exists between enhanced radiosensitization and conditions where elevated levels of NO and up-regulated NOS are contributors to tumor progression. The relationship between NOS expression and tumor growth is evident in the literature from studies with a variety of cancer types including: (1) human oral squamous cell carcinoma [10,40], (2) gastric carcinoma [41], (3) lymph node metastases, and most significantly for this current work, (4) breast cancer, to a point that it is a universal property for human solid tumors [7,[15][16][17][42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a dichotomy exists between enhanced radiosensitization and conditions where elevated levels of NO and up-regulated NOS are contributors to tumor progression. The relationship between NOS expression and tumor growth is evident in the literature from studies with a variety of cancer types including: (1) human oral squamous cell carcinoma [10,40], (2) gastric carcinoma [41], (3) lymph node metastases, and most significantly for this current work, (4) breast cancer, to a point that it is a universal property for human solid tumors [7,[15][16][17][42][43][44][45].…”
Section: Resultsmentioning
confidence: 99%
“…In prior work, our laboratory explored expression levels of NOS and nitrotyrosine in various carcinomas [9][10][11][12]. Work by other reserachers has demonstrated that NO is overexpressed in multiple cancer types [13][14][15][16][17][18][19]. In vitro studies have alluded to there being NO concentration levels, which when reached, result in phenotypic changes in tumors [20].…”
Section: Introductionmentioning
confidence: 99%
“…Loibl et al further demonstrated that while none of the benign lesions were positive for iNOS, 67% in situ carcinomas and 61% invasive lesions showed iNOS tumour cell staining. eNOS expression was found in 33 invasive lesions (61%) [22]. Both iNOS expressing lesions and eNOS expressing lesions showed strong co-expression (p=0.0008).…”
Section: Nitric Oxide Synthase Expression In Tumoursmentioning
confidence: 95%
“…NO biosynthesis was significantly greater for grade III tumours as compared with grade II in specimens from 10 breast cancer tissues. Recently, three relatively large scale studies [20][21][22], suggested that iNOS is not only expressed in stromal cells and macrophages in the tumour, but also in tumour cells themselves (Tab 1). Reveneau et al reported NOS activity in 27 of 40 tumours studied [20].…”
Section: Nitric Oxide Synthase Expression In Tumoursmentioning
confidence: 99%
“…[15][16][17] Expression of the eNOS gene appears to be high in a normal mammary epithelium cell line (i.e., HMEC) but downregulated in breast carcinoma cell lines (i.e., ZR-75-9a1, ZR-PR-LT, and MCF-7 ADR). 18,19 However, there are contrasting results from studies of eNOS expression in breast cancer tissues, [20][21][22][23] most likely because many endogenous and exogenous factors, including genetic variation in the eNOS gene, influence eNOS protein expression levels.…”
mentioning
confidence: 99%